Sustainability strategy: Strengthening SDGs desa through CSR communication program - Afnan, Dikhorir; Wijaya, Mahendra; Kartono, Drajat Tri; Wibowo, Agung (Goodwood Publishing, 2024)
Purpose: This study aims to examine the sustainability strategy of Indocement Tunggal Prakarsa Cirebon West Java in implementing the sustainability commitment of Heidelbergcement Group 2030 (SC2030) which contains long-term commitments and targets of the group including the company until 2030. Research Methodology: This study used a qualitative case study approach. As a research instrument, I played an active role in collecting data through direct interaction with informants to conduct interviews and observations and analyze available documents. The object of research or social situations in this study focuses on the activities of people in a particular place. Results: The findings obtained from this study are that community empowerment programs implemented sustainably through Bilikom CSR are key elements in building national economic resilience. Through Bilikom's CSR, companies can achieve development goals at the village level. However, in practice, sustainability strategies become good neighbors through Bilikom's CSR programs, with occasional misperceptions in designing and implementing programs that have been prepared together. Limitations: The limitations of this study include social, environmental, and economic aspects. Contributions: This research is expected to contribute to the development of a new science. This research is also very useful for the government in developing and managing an ideal communication system to implement community empowerment programs Novelty: The novelty of this study is that strengthening SDGs in villages can create a positive impact in reducing economic inequality, improving the quality of life of the community, and supporting sustainable natural resource management.